2020
DOI: 10.3928/23258160-20201005-02
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Epiretinal Membrane Removal Due to Combined Hamartoma of the Retina and RPE

Abstract: BACKGROUND AND OBJECTIVE: To evaluate the surgical outcomes of epiretinal membrane (ERM) associated with combined hamartoma of the retina and retinal pigment epithelium (CHRRPE) after vitrectomy and membrane peel. PATIENTS AND METHODS: A retrospective review of 15 patients who underwent pars plana vitrectomy with membrane peeling. No plasmin enzyme was used. RESULTS: The mean age at surgery wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Surgical data are usually restricted to smaller series and case reports. The largest series by Sun et al 8 included 15 patients treated with PPV. They reported visual improvement in 14 eyes (93%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgical data are usually restricted to smaller series and case reports. The largest series by Sun et al 8 included 15 patients treated with PPV. They reported visual improvement in 14 eyes (93%).…”
Section: Discussionmentioning
confidence: 99%
“…Several case series with small sample sizes reported favorable outcomes after pars plana vitrectomy (PPV) of CHRRPE. 8,11–14…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 small case reports (43 patients) have shown that surgery results shows good visual outcomes (success rate >70%). 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 It was found that 39 of the 43 patients (90.7%) had postoperatively improved in VA. Because of rarity of the disease the largest cohort study was published by Sun et al. 30 in 2020 with only 15 patients.…”
Section: Surgical Management Of Epiretinal Membranementioning
confidence: 96%